The Effect of JULO on the Well-Being of Grab Drivers in Malang City - Felik Sad Windu Wisnu Broto; Sandyka Rama Wijaya (International Journal of Asian Business and Management, 2024)
This study aims to analyze the impact of online loans on the welfare of GRAB drivers in Malang City. Using a quantitative approach, data were collected through a survey of 45 drivers who met specific criteria, such as being single and having taken out a loan with JULO within the past year. The analysis reveals that online loans have a significant impact on the welfare of GRAB drivers. However, the study finds that while online loans can provide financial benefits to drivers, their overall impact on welfare is limited. This indicates that driver welfare is influenced not only by access to online loans but also by other more significant factors. Therefore, policies and programs designed to enhance driver welfare should consider broader factors such as job stability, adequate income, and access to social services